A two-state comparative implementation of peer-support intervention to link veterans to health-related services after incarceration: a study protocol - Molly M. Simmons; Benjamin G. Fincke; Mari-Lynn Drainoni; Bo Kim; Tom Byrne; David Smelson; Kevin Casey; Marsha L. Ellison; Christy Visher; Jessica Blue-Howells; D. Keith McInnes (BMC, 2017)
Abstract Background Approximately 600,000 persons are released from prison annually in the United States. Relatively few receive sufficient re-entry services and are at risk for unemployment, homelessness, poverty, substance abuse relapse and recidivism. Persons leaving prison who have a mental illness and/or a substance use disorder are particularly challenged. This project aims to create a peer mentor program to extend the reach and effectiveness of reentry services provided by the Department of Veterans' Affairs (VA). We will implement peer support for reentry veterans sequentially in two states. Our outcome measures are 1) fidelity of the intervention, 2) linkage to VA health care and, 3) continued engagement in health care. The aims for this project are as follows: (1) Conduct contextual analysis to identify VA and community reentry resources, and describe how reentry veterans use them. (2) Implement peer-support, in one state, to link reentry veterans to Veterans' Health Administration (VHA) primary care, mental health, and SUD services. (3) Port the peer-support intervention to another, geographically, and contextually different state. Design This intervention involves a 2-state sequential implementation study (Massachusetts, followed by Pennsylvania) using a Facilitation Implementation strategy. We will conduct formative and summative analyses, including assessment of fidelity, and a matched comparison group to evaluate the intervention's outcomes of veteran linkage and engagement in VHA health care (using health care utilization measures). The study proceeds in 3 phases. Discussion We anticipate that a peer support program will be effective at improving the reentry process for veterans, particularly in linking them to health, mental health, and SUD services and helping them to stay engaged in those services. It will fill a gap by providing veterans with access to a trusted individual, who understands their experience as a veteran and who has experienced justice involvement. The outputs from this project, including training materials, peer guidebooks, and implementation strategies can be adapted by other states and regions that wish to enhance services for veterans (or other populations) leaving incarceration. A larger cluster-randomized implementation-effectiveness study is planned. Trial registration This protocol is registered with clinicaltrials.gov on November 4, 2016 and was assigned the number NCT02964897 .